Deconstructing Diverse E-Commerce Business Models and Pathways to Tax and Accounting Compliance (Journal of economic and management development research, 2025)
As the digital economy deepens, the e-commerce sector has evolved from a single transaction form into a heterogeneous ecosystem of business models. Differences in operating logic and profit pathways across these models directly lead to varying complexity in accounting and taxation and to differentiated compliance risks. This paper systematically delineates eight core models—traditional e-commerce (B2B, B2C, C2B, C2C, O2O) and emerging formats (live-streaming e-commerce, community/direct selling, and private-domain sales)—and concentrates on key finance-and-taxation issues under each model, including revenue recognition, cost allocation, and tax treatment. Drawing on applicable accounting standards and tax policies, we propose targeted compliance strategies to guide the design of fit-for-purpose tax and accounting management systems for e-commerce enterprises.
Keywords: e-commerce models; tax and accounting compliance; revenue recognition; cost allocation; tax treatment